Landasan Akademik Program Merdeka Belajar Dalam Perspektif Psikologi Pendidikan dan Psikologi Pendidikan Islam - Anisa, Zainiya; Kholisussa'di, Kholisussa'di (Program Studi Pendidikan Luar Sekolah, 2024)
Abstract: To improve the quality of Indonesian Education, Mr. Nadiem Makarim as the Minister of Education sparked the independent learning program and an independent campus. Each concept must be known in advance regarding its academic foundation so that misunderstandings do not occur. So this article discusses how the concept of independent learning and the philosophical basis of the independent learning program. the research method used to collect the information is a literature study. So it was found that the independent learning program instilled several concepts from educational psychology from the theory of constructivism, progressivism and humanism. Then it is also adrift with the psychology of Islamic education in the hadith of the Prophet Muhammad and Al Ghazali's philosophy of science.Keywords: Free Learning, Educational Psychology, Islamic Educational Psychology.Abstrak:Â Untuk meningkat kualitas Pendidikan Indonesi pak Nadiem Makarim selaku Menteri Pendidikan Mencetuskan mengenai program merdeka belajar dan kampus merdeka. Setiap konsep harus diketahui terlebih dahulu mengenai landasan akademiknya agar tidak terjadi miskonsepsi. Sehingga artikel ini membahasan mengenai bagaimana konsep merdeka belajar dan landasan filosofis program merdeka belajar. metode penelitian yang digunakan untuk mengumpulkan informasinya adalah studi kepustakaan. Sehingga ditemukan hasil bahwa program merdeka belajar menanamkan beberapa konsep dari psikologi Pendidikan dari teori konstruktivisme, progressivismen dan humanisme. Kemudian terpaut juga dengan psikologi pendidikan islam yang ada dalam hadis Rasulullah saw dan filsafat ilmu Al Ghazali.Kata Kunci; Merdeka Belajar, Psikologi Pendidikan, Psikologi Pendidikan Islam.